(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Rapid changing in life style such as change in food habits, complexity in living has resumed no. of diseases in human being. The conventional method of treating these diseases is not effective. Hence no. of alternatives therapies comes into existence. Ozone therapy is one such method that comes into light from last decades. Priming result obtained has being observed with application of ozone particularly in the treatments of wounds heart diseases cancer, HIV. An attempt has been much in the paper to evaluate the effectiveness and feasibility of ozone application for the curing of Heart diseases.